IMPLEMENTATION OF THE COINCIDENCE FREQUENCY METER ON FPGA - PETRUSHAK, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Means of measuring various parameters and technical characteristics of radio equipment have always occupied leading positions in science and technology. Without an accurate definition of the relevant values, it is impossible to build modern high-quality radio communication systems, radar, navigation ground and satellite systems. In ultrasound diagnostics, which are used in medicine, the speed of blood flow in vessels is studied by determining the frequency of the reflected signal. At the same time, it is necessary to use high-speed frequency measurement tools in systems with active sensors used in telecommunication networks based on Internet of Things technology. For example, in active radar, using the frequency of the reflected signal, it is possible to calculate not only the coordinates, but also the circular speed of the moving target. Modern research is aimed at improving the metrological and technical indicators of existing measuring devices, in particular at developing new methods for correcting the characteristics of the transformation of the measuring channel, which is their main component. At the same time, most digital frequency meters are built on the method of counting the number of pulses N with an unknown period Tx that arrive at the input of the device during a calibrated time interval. All this leads to an increase in measurement time and requires additional hardware costs for fast processing of measurement results. The coincidence method belongs to vernier methods and is promising for use when measuring the frequency of periodic signals. This paper points out the shortcomings of known methods of measuring the frequency of a periodic signal. On the basis of the well-known method of coincidence, a functional scheme of a 16-bit device for measuring frequency, which is implemented on the basis of a FPGA from Intel (Altera), has been developed. The developed coincidence frequency meter has a dynamic range of 96dB. Representation of time diagrams obtained in the Quartus Prime 18.0 automated design environment and confirming the operability of the developed functional scheme of the 16-bit device for frequency measurement by the coincidence method. An analytical dependence for determining the frequency of a periodic signal during frequency measurement by the coincidence method is presented.